A new approach to the epoxidation of natural rubber through a sonochemical method - Lorwanishpaisarn N. (2023)
In this study, epoxidized natural rubber (ENR) was synthesized using a sonochemical method. Acoustic cavitation was employed for the epoxidation reaction instead of heat and agitation. The effects of reaction time and temperature on the epoxidation degree (EPD) were studied. The chemical structure and EPD of ENR were assessed by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR) techniques. At low reaction times (≤45 min), the EPD was independent of the reaction temperature but tended to increase with increasing reaction time. However, at sufficiently long reaction times (>45 min), the EPD depended on both reaction time and temperature, i.e., it increased slightly with an increase in reaction time up to 60 min before leveling off at the reaction temperatures of 20 °C and 30 °C. However, at a higher reaction temperature (40 °C), it tended to decline slowly with increasing reaction time, possibly due to the ring-opening reaction. The highest EPD, at approximately 30%, was achieved when synthesized by a sonochemical method at 30 °C for 60 min, which is equivalent to that of the ENR synthesized by a conventional method at 60 °C for 6 h. The properties of the raw ENR samples (with ∼30% epoxidation) prepared by different methods were also investigated. It was found that the ENR sample prepared by the sonochemical method possessed a slightly higher viscosity, initial plasticity number, and plasticity retention index than the ENR sample prepared by the conventional method. The results reveal the potential of the sonochemical method to supplant the conventional method for ENR synthesis, as it requires a considerably lower reaction temperature and time.